Enhancer-Derived lncRNAs Regulate Genome Architecture: Fact or Fiction?. Issue 6 (June 2017) - Fanucchi, Stephanie; Mhlanga, Musa M.
Abstract : How does the non-coding portion of the genome contribute to the regulation of genome architecture? A recent paper by Tan et al. focuses on the relationship between cis -acting complex-trait-associated lincRNAs and the formation of chromosomal contacts in topologically associating domains (TADs).